On one class of algebras - Zhuchok, Yul.V. (Algebra and Discrete Mathematics, 2014)
In this paper a g-dimonoid which is isomorphic to the free g-dimonoid is given and a free n-nilpotent g-dimonoid is constructed. We also present the least n-nilpotent congruence on a free g-dimonoid and give numerous examples of g-dimonoids.